Prediction of bone mechanical properties using MRI - Cheah, Yan Ying. (2012)
The project’s main aim was to find out the relationship between mechanical properties of bone with Magnetic Resonance Imaging (MRI) parameters and bone mineral density (BMD), so as to investigate the possibility of using MRI to predict mechanical competence of bones in patients. To achieve this aim, MRI and Computed Tomography are used to obtain parameters regarding the structure. These parameters were then correlated with mechanical properties of the bone.